Capacity of patients with brain metastases to make treatment decisions. Issue 11 (23rd January 2015) - Triebel, Kristen L.; Gerstenecker, Adam; Meneses, Karen; Fiveash, John B.; Meyers, Christina A.; Cutter, Gary; Marson, Daniel C.; Martin, Roy C.; Eakin, Amanda; Watts, Olivia; Nabors, Louis B.
Abstract: Objective: The aim of this study was to investigate medical decision‐making capacity (MDC) in patients with brain metastases. Methods: Participants were 41 adults with brain metastases with Karnofsky Performance Status scores of ≥70 who were recruited from an academic medical center and 41 demographically matched controls recruited from the community. We evaluated MDC using the Capacity to Consent to Treatment Instrument and its four clinically relevant consent standards ( expressing a treatment choice, appreciation, reasoning, and understanding ). Capacity impairment ratings (no impairment, mild/moderate impairment, and severe impairment) on the consent standards were also assigned to each participant with brain metastasis using cutoff scores derived statistically from the performance of the control group. Results: The brain metastasis patient group performed significantly below controls on consent standards of understanding and reasoning. Capacity compromise was defined as performance ≤1.5 standard deviations below the control group mean. Using this definition, approximately 60% of the participants with brain metastases demonstrated capacity compromise on at least one MDC standard. Conclusion: When defining capacity compromise as performance ≤1.5 standard deviation below the control group mean, over half of patients with brain metastases have reduced capacity to make treatment decisions. This impairment is demonstrated shortly after initial diagnosis of brain metastases and highlights the importance of routine clinical assessment of MDC following diagnosis of brain metastasis. These results also indicate a need for the development and investigation of interventions to support or improve MDC in this patient population. Copyright © 2015 John Wiley & Sons, Ltd.